Cardiovascular disease and oral contraceptives - Razzeto Ríos, Luis (2015)
In Western countries, cardiovascular disease is the leading cause of death in both women and men. Half of these deaths are attributable to coronary heart disease, mainly caused by atherosclerosis, an obstructive process that begins early in humans and persists through the life of patients who suffer. Previous retrospective studies showed an increase of approximately 4 times in myocardial infarction in women who took oral contraceptives. This review aims to upgrade the relationship may have on the cardiovascular system using oral contraceptives.